(untitled) (Praxis Educativa, 2023)
In this article we discuss results of research carried out in a secondary school in a neighborhood of the Metropolitan Area of Buenos Aires characterized by the presence of multiple garbage dumps. From the analytical series "la quema-te re-quema" we try to problematize some of the multiple conditions of becoming a teacher in contexts of urban poverty and environmental degradation. We propose that the teaching task in these spaces is configured, on the one hand, by the transfer of responsibilities to individuals and institutions, typical of the managerial logics that characterize current societies and, on the other, by the interconnections that are established daily in a precarious materiality, typical of neighborhoods located between dumps. It is from this affection that we try to approach the understanding of how urban and school inequality is expressed on a daily basis.